2021
DOI: 10.1590/1516-4446-2020-0986
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for post-traumatic stress, anxiety, and depression in sepsis survivors after ICU discharge

Abstract: Objective: Sepsis survivors present a wide range of sequelae; few studies have evaluated psychiatric disorders after sepsis. The objective of this study was to define the prevalence of and risk factors for anxiety, depression and post-traumatic stress disorder (PTSD) symptoms in sepsis survivors. Method: Anxiety, depression and post-traumatic stress symptoms in severe sepsis and septic shock survivors 24 h and 1 year after intensive care unit (ICU) discharge were assessed using the Beck Anxiety/Depression Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…It has been reported that more than 19 million septic patients each year ( Prescott and Angus, 2018 ). As one of the major manifestations of SAE, long-term mental health issues affect as many as 58% of surviving septic patients ( Prescott and Angus, 2018 ; Calsavara et al, 2021 ), leading to poor quality of life and a heavy economic burden. However, the concrete mechanism of long-lasting mental disorders in septic patients is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more than 19 million septic patients each year ( Prescott and Angus, 2018 ). As one of the major manifestations of SAE, long-term mental health issues affect as many as 58% of surviving septic patients ( Prescott and Angus, 2018 ; Calsavara et al, 2021 ), leading to poor quality of life and a heavy economic burden. However, the concrete mechanism of long-lasting mental disorders in septic patients is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more than 19 million individuals develop sepsis each year [16]. As one of the major manifestations of SAE, long-term mental dysfunction affects 29 % of surviving septic patients [16,17], which leads to poor quality of life and a heavy economic burden. However, the concrete mechanism of long-lasting mental impairments in septic patients is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a preexisting psychiatric history are at greater risk for developing any combination of these distressing outcomes while in the ICU 75,76 . Recent studies also suggest that psychological symptoms may continue to be elevated after ICU stays 71,77‐80 …”
Section: Literature Review/methodsmentioning
confidence: 99%
“…Moreover, diagnostic criteria for each of these disorders include symptoms pertaining to cognition (eg, difficulty concentrating) 13 . These symptoms and disorders often present comorbidly in ICU survivors (eg, PICS) 78,87 and further underscore the complex and multifactorial etiology of ICU‐related cognitive impairment 88 …”
Section: Literature Review/methodsmentioning
confidence: 99%
See 1 more Smart Citation